Analysis of Teachers' Work Discipline at Sunan Ampel Menganti Vocational High School - Siti Mu'awanah; Roziana Ainul Hidayati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
In education, teacher work discipline is an important element because it directly relates to the quality of learning and the achievement of educational goals. Teachers must demonstrate professional behavior consistent with the school's rules and norms. However, some teachers still arrive late, violate school regulations, and are less responsible in their duties. The purpose of this study is to understand the impact of indiscipline on teacher performance and strategies to improve teacher discipline. This type of research is descriptive qualitative research, data collection uses semi-structured interviews, data analysis uses the Miles & Huberman model, and member checks are used for data validity. The results of this study indicate that teacher indiscipline has negative impacts on themselves, fellow teachers, students, and the school. School efforts by implementing a fingerprint system, regular evaluations, and regulations regarding violation sanctions must be reinforced. There should also be a reward system for disciplined teachers. Research findings suggest that school policies need to integrate discipline monitoring and provide rewards to motivate teachers to be more effective in improving teacher discipline.